2003
DOI: 10.1093/pcp/pcg090
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Induced Changes in Viscoelastic Properties of Sorghum Root Cell Walls

Abstract: ;Silicon is deposited in the endodermal tissue in sorghum (Sorghum bicolor L. Moench) roots. Its deposition is thought to protect vascular tissues in the stele against invasion by parasites and drying soil via hardening of endodermal cells. We studied the silicon-induced changes in mechanical properties of cell walls to clarify the role of silicon in sorghum root. Sorghum seedlings were grown in nutrient solution with or without silicon. The mechanical properties of cell walls were measured in three separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 22 publications
4
86
0
1
Order By: Relevance
“…Hattori et al (2003) also reported that Si promoted root elongation in sorghum. The Si-enhanced cell-wall extensibility in the growing zone of the roots is probably one of the causal factors promoting root elongation.…”
Section: Discussionmentioning
confidence: 88%
“…Hattori et al (2003) also reported that Si promoted root elongation in sorghum. The Si-enhanced cell-wall extensibility in the growing zone of the roots is probably one of the causal factors promoting root elongation.…”
Section: Discussionmentioning
confidence: 88%
“…It is already known that Si decreases cell wall thickness in leaves, by increasing its extensibility and thus general growth (HOSSAIN et al, 2002a); therefore, it is plausible to state that this may also be effective other plant organs. Hattori et al (2003) studied some changes induced by Si on mechanical properties in cell walls of sorghum roots and found that this element improved their expansion capacity in apical and subapical regions. Findings from those authors emphasize Si role in root growth, as also observed in this study (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Silicon plays two separate functions in root cell walls, strengthening the endodermal cell walls in the mature basal region and keeping the young expanding cell walls extensible in the apical region of the roots (Hattori et al 2003). The application of silicon seems to be quite beneficial to plants grown under drought conditions by encouraging the development of a big root system and providing protection to roots against soil drying.…”
Section: Discussionmentioning
confidence: 99%
“…Si benefits to drought tolerance in wheat (Gong et al 2005), maize (Li et al 2007;Yong et al 2007), sorghum (Hattori et al 2003(Hattori et al , 2005 and salt tolerance of barley, tomato and cucumber (Liang et al 2003;Al-Aghabary et al 2004;Zhu et al 2004) have been related to its effect on the antioxidant enzyme activity. Gong et al (2005) reported that application of Si increased the activities of SOD, CAT and GR, the fatty acid unsaturation of lipids, and the contents of photosynthetic pigments and soluble proteins as well as total thiols under drought stress on wheat, whereas the content of H 2 O 2 , activity of acid phospholipase (AP) and oxidative stress of proteins were decreased by applying Si compared with those of non-Si treatments under drought stress.…”
mentioning
confidence: 99%